2018
DOI: 10.1155/2018/8031259
|View full text |Cite
|
Sign up to set email alerts
|

Toeplitz Operators with Horizontal Symbols Acting on the Poly-Fock Spaces

Abstract: We describe the C⁎-algebra generated by the Toeplitz operators acting on each poly-Fock space of the complex plane C with the Gaussian measure, where the symbols are bounded functions depending only on x=Re  z and have limit values at y=-∞ and y=∞. The C⁎ algebra generated with this kind of symbols is isomorphic to the C⁎-algebra functions on extended reals with values on the matrices of dimension n×n, and the limits at y=-∞ and y=∞ are scalar multiples of the identity matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…3. In [23,26,29], all matrices have the same order n, whereas in our Theorem 1.1 the matrices have orders 1, 2, . .…”
Section: Introduction and Main Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…3. In [23,26,29], all matrices have the same order n, whereas in our Theorem 1.1 the matrices have orders 1, 2, . .…”
Section: Introduction and Main Resultsmentioning
confidence: 81%
“…Comparing our Theorem 1.1 with the main results of [23,26,29], we would like to point out three differences.…”
Section: Introduction and Main Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…They considered an orthonormal basis of normalized complex Hermite polynomials to prove that the radial operators are diagonal. In [4], the authors studied Toeplitz operators acting on the one-dimensional poly-Fock space with horizontal symbols such that the limit values at x = ∞ and x = −∞ exist. They proved that the C * -algebra generated with this class of symbols is isomorphic to the C * -algebra of functions on ℝ with values on the m × m matrices, whose limit value at x = ∞ and x = −∞ are equal to some scalar multiples of the identity matrix.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in [17,18], the authors studied Toeplitz operators on the Fock space F 2 1 ðℂÞ with radial and bounded horizontal symbols; they found that spectral functions are uniformly continuous with respect to an adequate metric. Taking horizontal symbols having one-side limits at x = ±∞, in [19,20], the authors studied Toeplitz operators acting on poly-Fock spaces F 2 k ðℂÞ; they found the spectrum of the C * -algebra generated by such Toeplitz operators. Even though the authors described the C * -algebras generated by all spectral functions, the spectrum of the algebras is not fully understood in some cases; for this reason, additional conditions on the symbols are imposed.…”
Section: Introductionmentioning
confidence: 99%